2000
DOI: 10.2525/ecb1963.38.273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transplant Container and Solanam Rootstocks on the Incidences of Overgrowth and Unmarketable Fruits in Tomato Plants Planted with Plug Seedlings.

Abstract: The incidences of overgrowth and unmarketable fruits were compared between tomato autografts planted with 50 mL plug and those with 800 mL pot (control), and the regulation of such incidences were tried with Solanum rootstocks. Planting with plug promoted the early growth of tomato plants and the growth was regulated by Solanum rootstocks. S. melongena rootstock suppressed the overgrowth and kept vigor similarly to that of the control autograft, whereas S. integrifolium and S. torvum rootstocks decreased the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These results confirm previous data obtained by Oda et al (2000), who studied the effect of different rootstocks on tomatoes in which the growth of scions was depressed and where stems at the graft union thickened markedly 18 weeks after grafting. In contrast, another study (Oda et al, 2005) indicated that little or no effect of rootstocks species appeared on the growth of tomato plants scions except for an increase of stem thickening at the graft union.…”
Section: Discussionsupporting
confidence: 94%
“…These results confirm previous data obtained by Oda et al (2000), who studied the effect of different rootstocks on tomatoes in which the growth of scions was depressed and where stems at the graft union thickened markedly 18 weeks after grafting. In contrast, another study (Oda et al, 2005) indicated that little or no effect of rootstocks species appeared on the growth of tomato plants scions except for an increase of stem thickening at the graft union.…”
Section: Discussionsupporting
confidence: 94%
“…'Hongmianmiyou' and 'Huangjinmiyou' were grafted onto Poncirus trifoliata (Gong et al, 2016). Tomato/pepper healing junction showed the asynchronous stem bulging 30 days after grafting (Masayuki et al, 2000;Thomas et al, 2021), which was also observed in graft incompatible melon (Cohen et al, 2007;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…e idea of grafting tomato onto eggplant is not new and has been successfully performed in the past in tropical conditions [12]. Moreover, it can increase marketable yield [13], manage soilborne diseases [14], and improve alkalinity tolerance [15], in accordance with the specific characteristics and problems of each agroecosystem. e selection of compatible rootstocks using local genetic resources is expected to address local issues and be more practical than using imported resources.…”
Section: Introductionmentioning
confidence: 99%